Pemanfaatan Sistem Informasi Geografis Untuk Pemetaan Lahan Pertanian di Kecamatan Kembaran, Banyumas, Jawa Tengah : The Utilization of Geographic Information Systems for Agricultural Land Mapping in Kembaran District, Banyumas, Central Java - Wahab, Luthfi; Kurniawan, Anry (Department of Agriculture, Subang State Polytechnic, Indonesia, 2023)
Kembaran District is one of the districts located in Banyumas Regency, Central Java Province, Indonesia. Kembaran District has a total area of approximately 126.74 km² and consists of 15 villages. The majority of the population in Kembaran District work as farmers, with agriculture being one of the main economic sectors. Rice, corn, and other crops are common agricultural commodities in this area. This research aims to map the potential agricultural land in Kembaran District, Banyumas, Central Java using Geographic Information System (GIS). The method used in this research is a descriptive method to analyze and match the data of the study area with the criteria. In this research, spatial data is obtained from various sources, including satellite imagery, topographic maps, and field data. The attribute data of the land is the agricultural land area. Subsequently, the data is processed and analyzed using GIS software to map agricultural land in Kembaran District. The results of the research show that the use of GIS in mapping agricultural land in Kembaran District can provide accurate information about the distribution of land in the area. The findings of this research have important implications for the management of agricultural land in Kembaran District and its surrounding areas. The results of overlay analysis between village boundaries and agricultural land in Kembaran District yielded the following results: the village with the largest agricultural land area is Purwodadi Village with an area of 186.29 Ha, and the village with the smallest agricultural land area is Sambeng Wetan Village with an area of 59.67 Ha. Meanwhile, the average agricultural land area of the 16 villages in Kembaran District is 117.72 Ha.